THE IMPLEMENTATION OF GAMES-BASED LEARNING IN IMPROVING THE MOTIVATION FOR ENGLISH LEARNING AT SMPN 5 SATAP TAMAKO - cindy kampohiang; Maya Pinkan Warouw; Dewi Christa Kobis (Paratext: International Journal of Language and Literature, 2025)
This research is entitled "Implementation of Game-Based Learning in Improving English Learning at SMPN 5 Satap Tamako Students." The purpose of this study is to describe the implementation of game-based learning in SMPN 5 Satap Tamako students and analyze how the implementation of game-based learning is applied at SMPN 5 Satap Tamako. The research method used is a classroom action research method in accordance with Kemmis and McTaggarts in Burn (2010), the research was carried out in two cycles, the first cycle was carried out twice a meeting with the name of the game guess the meaning of objects in the classroom and did not experience an increase in motivation to learn English so that the second cycle method was carried out with two meetings of the game called the game guess the profession in the second cycle experienced an increase in motivation to learn English at SMPN 5 Satap Tamako.